The Association between Fourier Parameters and Clinical Parameters in Myopic Children Undergoing Orthokeratology. (2nd November 2021) - Wang, Di; Wen, Dejia; Zhang, Bin; Lin, Weiping; Liu, Guihua; Du, Bei; Lin, Fang; Li, Xiaorong; Wei, Ruihua
ABSTRACT: Purpose : To explore how Fourier parameters are associated with axial length growth (ALG) and clinical parameters in children who underwent orthokeratology. Materials and Methods : A total of 267 children received orthokeratology. Baseline cycloplegic autorefraction was performed. Axial length was measured at baseline and one year after the lens dispatch, and the difference was defined as ALG. Corneal topography was performed at the same two visits. Central treatment zone (CTZ) was identified from the difference between the two tangential maps, and its center distance to corneal center was defined as decentration. A relative refractive corneal power (RCRP) map was derived by subtracting the center value from every point on the one-year axial map. It was decomposed into 3 Fourier components: a mean (F0), a single-cycle sinewave (F1), and a double-cycle sinewave (F2). Linear regressions were used to reveal the association between ALG and these parameters. Results : At baseline, the age was 10.18 ± 1.48 year, spherical equivalent (SE) was – 3.10 ± 1.15D, astigmatism was 1.17 ± 0.58D, and axial length was 24.69 ± 0.81 mm. The mean ALG was 0.181 ± 0.22 mm. In multiple regression, ALG was negatively associated with F1 ( p < .001), not F0 and F2. Amplitude-wise, F0 and F1 were correlated with decentration ( p < .01) and SE ( p < .01), and F2 was associated with astigmatism ( p < .001). Direction-wise, F1 was correlated with decentration ( p < .001) and F2 was associated with astigmatism ( p < .001). Conclusions : Among Fourier parameters, F0 and F1 were negatively associated with ALG in myopic children undergoing orthokeratology. Their associations to SE and CTZ decentration may partially explain the effect on ALG retardation.